Die Flüchtlingskrise 2015 im Spiegel der polnischen Presse. Eine Analyse von Nominationsstrategien: An analysis of nomination strategies - Smykała, Marta (Stylistyka, 2020)
The word refugees was chosen the word of the year 2015 in many European countries (in Poland, Germany, Austria, Czech Republic, France and Russia). This word as well as other candidates were at that time – in the truest sense of the word – on everyone’s lips. They were literally hitting the headlines. No surprise. Millions of people, mainly from the Middle East and North Africa, who wanted to be let in, were knocking at the gates of Europe. In the media discourse this phenomenon was called ‘crisis’ (the refugee crisis, the migration crisis). This article aims to analyse the language profiling of the phenomenon itself and the people it referred to both in Polish and German press, i.e. the refugees, at the beginning of the crisis, that is in the summer of 2015.